Peranan Sistem Aplikasi FASt Terhadap Efektivitas Pengendalian Intern Piutang Dagang (Studi Kasus pada PT KEA Panelindo) - Sufriyanti, Fitri; Muanas, Muanas (Institut Bisnis dan Informatika Kesatuan, 2018)
The purpose of this study was to determine the procedures of credit sales and internal controls of accounts receivable, to determine how the application of FAST system acts as an internal control of accounts receivable, and to understand what the impact of the role of FAST application system on the effectiveness of internal control of accounts receivable. The method used is descriptive qualitative method. This research was taken place at Kea Panelindo, from 13 April to 13 July 2016. Results of research showed that the role of FAST application system FAST (Finance Accounting System) on the effectiveness of internal control accounts receivable at PT. Kea Panelindo proved that the system is sufficient. It can be seen from the components of accounts receivable and the procedures carried out by the company have been in accordance with standard operational procedures adopted by the company. Control of the company's accounts receivable can be monitored through documents of credit sale agreement, the addition of accounts receivable, collection of accounts receivable, cash receipts from the repayment of accounts receivable, the elements of internal control in companies such as the control environment, risk assessment, control activities, information and communication, and monitoring.